Effect of time of grafting and scion varieties on success of graftage in guava (Psidium guajava) (Current Horticulture, 2024)
The experiment was conducted at College of Horticulture and Forestry, Rani Lakshmi Bai Central Agricultural University, Jhansi, during 2019-20 to see the effect of time of grafting and source of scion on grafting performance in guava (Psidium guajava L.). Treatments comprised four time of grafting, viz. T1: 1st fortnight of January, T2: 2nd fortnight of January, T3: 1st fortnight of February and T4: 2nd fortnight of February, and four different scion varieties viz. S1: Allahabad Safeda, S2: L-49, S3: Lalit and S4: Shweta. Significant differences of time of grafting and source of scion were observed in different grafting and growth parameters. The maximum bud sprouting (97.8%) was noted in T2S2, 2nd fortnight of January + L-49, which found at par with T4S1, 2nd fort night of February + Allahabad Safeda (95.6%), whereas minimum bud sprouting was noted in T1S4 1st fortnight of January + Shweta (53.3%). The highest final survival (95.6%) obtained from T2S2 (2nd fortnight of January + L-49) which was at par with T3S1 and T3S2, whereas lowest final survival was observed in 1st fortnight of January + Shweta (53.3%).
Keywords: Time of grafting; Scion; Wedge grafting; Bud sprouting; Seedlings